Haemocyte parameters and haemolymph chemistry in the black shell Anadara tuberculosa broodstock (Arcoida: Arcidae) - Espinoza, Karen (2022)
In this work we studied the health status of wild populations of the black shell Anadara tuberculosa, haemocyte parameters (viability, total and differential count, lysosomal stability, osmotic fragility) and blood chemistry (haemoglobin-Hb, proteins, triglycerides, glucose, lactate dehydrogenase-LDH and catalase-CAT). Haemolymph was extracted from apparently healthy wild broodstock collected from Corazón Island, Chone River, Ecuador. Cell viability was high, with 5 morphotypes present: erythrocytes (74%), colorless granulocytes (6%), amebocytes (3%), hyalinocytes (12%), blastocytes (5%). Haemocytes showed stable lysosomal membranes to neutral red for 240 min and a mean osmotic fragility (OF50) was 4.8‰. Hb, protein, lipid and glucose concentrations denote respiratory function and energy reserves during tidal changes. LDH activity is linked to anaerobic metabolism and CAT denotes the ability to maintain the redox balance of the immune system. The haemocitary parameters and haemolymph chemistry can serve as normal physiological reference indices in A. tuberculosa broodstock.